(untitled) (Forum Penelitian Agro Ekonomi, 2023)
Resilience has recently been widely used in academic, policy, and development discourses, but this concept has yet to be widely applied to agricultural issues. The shocks and challenges farmers face are diverse, ranging from natural disasters, climate change, price issues, and policies that do not favor farmers and agriculture. This research was conducted using the systematic literature review (SLR) method to overcome this knowledge gap, discover global trends in resilience research, and find key answers about the factors that determine the resilience of smallholder farmers. The number of metadata articles collected from Scopus.com is 720. Data analysis was done using Microsoft Excel and the Bibliometric application to capture global trends from existing research. Data collection was carried out using the Prisma Protocol. An in-depth analysis was conducted on 38 articles that discussed the resilience of smallholder farmers. Based on the results of our research, we found that extension, communication, and farmer organizations are the determining factors for increasing the resilience of smallholder farmers. This research recommends approaches and policies that can increase the role of extension, communication, and farmer organizations to increase the resilience of smallholder farmers.